Advancing water productivity monitoring: WaPLUGIN for the analysis and validation of FAO WaPOR data in QGIS - A. Dhonthi; F. H. Fonseca Aponte; Z. Nemer; C. Hadj Ali; M. Y. Tebbouche; H. Van Der Kwast (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2024)
The FAO WaPOR (Water Productivity Open Access Portal) is a significant initiative developed by the Food and Agriculture Organization of the United Nations (FAO). It provides extensive datasets derived from remote sensing, specifically aimed at monitoring water productivity in agriculture. The primary goal of WaPOR is to enhance water use efficiency and promote sustainable agricultural practices globally. Given the importance of this datasets and with the objective to streamline access to the datasets for users, we have developed WaPLUGIN. WaPLUGIN is a QGIS plugin designed to help users easily retrieve WaPOR datasets directly into QGIS environment and enables the computation of various performance metrics that are useful to assess efficiency of the irrigation schemes. This plugin is a useful tool which helps users and stakeholders to focus on the interpretation of the datasets and make subsequent decisions. The plugin also helps to download and process the WaPOR data.